2019
DOI: 10.1002/suco.201800242
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic studies on mechanics‐based shear capacity models for reinforced concrete beams with stirrups

Abstract: The efficiency of shear capacity models of reinforced concrete beams with stirrups depends on the assumed mechanism and in few cases depends also on critical shear crack angle prediction. In the present study, three mechanics‐based shear capacity models (the limit analysis‐based models presented by Nielsen and Hoang, and the Mari et al. model) are considered covering the range space of shear span to effective depth ratios greater than 2.5. The statistics of modeling error associated with these models are deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…When designing a structure with respect to robustness, it must also be taken into consideration that progressive collapses caused by extreme events are low-probability high-consequence phenomena [1]. In order to be able to accurately predict the structural response, it is important to study the progressive collapse behavior using a probabilistic approach, as it has been found that there is a significant influence of many uncertainties on the structural behavior, e.g., randomness from material properties, which is neglected by most existing studies [30][31][32][33][34][35][36][37][38][39][40][41][42]. However, in the three widely used approaches in relation to the quantification of the structural robustness, i.e., deterministic-based method, probabilisticbased method, and risk-based method [30,43,44], both the probabilistic-based method and the risk-based method require a reliability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…When designing a structure with respect to robustness, it must also be taken into consideration that progressive collapses caused by extreme events are low-probability high-consequence phenomena [1]. In order to be able to accurately predict the structural response, it is important to study the progressive collapse behavior using a probabilistic approach, as it has been found that there is a significant influence of many uncertainties on the structural behavior, e.g., randomness from material properties, which is neglected by most existing studies [30][31][32][33][34][35][36][37][38][39][40][41][42]. However, in the three widely used approaches in relation to the quantification of the structural robustness, i.e., deterministic-based method, probabilisticbased method, and risk-based method [30,43,44], both the probabilistic-based method and the risk-based method require a reliability analysis.…”
Section: Introductionmentioning
confidence: 99%